Whole‐Body Muscle Magnetic Resonance Imaging in Glycogen‐Storage Disease Type III. Issue 1 (24th April 2019) - Tobaly, David; Laforêt, Pascal; Perry, Ariane; Habes, Dalila; Labrune, Philippe; Decostre, Valerie; Masingue, Marion; Petit, Francois; Barp, Andrea; Bello, Luca; Carlier, Pierre; Carlier, Robert‐Yves
ABSTRACT: Introduction : The main objective of this study was to describe muscle involvement on whole‐body magnetic resonance imaging scans in adults at different stages of glycogen‐storage disease type III (GSDIII). Methods : Fifteen patients, 16–59 years of age, were examined on a 3‐T system. The examinations consisted of coronal and axial T1‐weighted images or fat images with a Dixon technique, and were scored for 47 muscles using Mercuri's classification. Muscle changes consisted of internal bright signals of fatty replacement. Results : Distribution across muscles showed predominant signal alteration in the lower limbs and postural muscles. This finding is consistent with the overall clinical presentation of GSDIII and the results of heatmap scores. Review of the MRI scans provided new information regarding recurrent muscle changes, particularly in the soleus, gastrocnemius medial head, and thoracic extensor muscles. Discussion : Whole‐body muscle imaging provides clinically relevant information regarding muscle involvement in GSDIII. A severity score may contribute to improved patient management. Muscle Nerve, 2019